Penerapan Pembelajaran Nearpod pada Mata Pelajaran PPKn di MTsN 2 Mataram - Nurmasita Nurmasita; M. Ismail; Ahmad Fauzan; Edy Herianto (MANAZHIM, 2022)
Learning using nearpod can make learning interactive, effective, innovative and besides that it can also increase students' motivation in learning. This study aims to determine the application of nearpod application learning in Civics subjects at MTsN 2 Mataram. This study uses a qualitative approach with descriptive type. Data collection techniques used are interviews, observation, and documentation. Based on the results of the study, it showed that the application of nearpod application learning in Civics subjects was carried out through 3 stages, namely the planning stage, the implementation stage and the evaluation stage. The supporting factors for implementing the nearpod application learning are ready-to-use materials, various features or content, student human resources, and learning motivation. While the inhibiting factors consist of the internet network and the limited number of students.